Pengekstrakan senarai bahan daripada perisian AutoCad 2000 - Norlina Udin @ Kamaruddin (2004)
This research studies on the pattern recognition technique that is used to produce a bill of materials from drawing objects. The object are drawn with the AutoCAD 2000. In this research, it was found that there are a variety of methods available to make this application more user-friendly. Nevertheles ActiveX (Visual Basic) method is used in their research together with Drawing Exchange Format (DXF) which is one of the standard for drawing exchange data. An automatic system to extract bills of materials which is called as AutoBOM is implemented to replace the manual system. The main objective of AutoBOM is to assist AutoCAD users especially an engineer to produce bills of material from one database. The beauty of AutoBOM is that it can exchange drawing file format from dwg to bitmap and dxf format automatically. Next, the object component can be recognized in the system through recognizing the respective blocks. Data concerning object component such as component block name and component level from dxf file will be extracted by the system. Apart from that, AutoBOM provide ease of use for the user to input detailed information of a object component such as its description. This description will be kept along with data component in a single database.